PENGARUH PEMBERIAN HERBAL MEDICINE TERHADAP KADAR HEMOGLOBIN MAHASISWI AKADEMI KEBIDANAN SYEKH YUSUF GOWA DI KEC. SOMBA OPU KAB. GOWA - Ny. Alhidayah (Voice of Midwifery, 2017)
This research aimed to investigate the effect of the herbal medicine treatment on the hemoglobin levels in female students of Syekh Yusuf Academy of Midwivery (AKBID), Gowa Regency.The research used the experimental method with the pre-post test design. The sampels comprising 60 respondens were chosen using the total sampling technique. The total samples were divided into two group 30 respondents were in the intervention group and 30 respondents in the control group.The data were analyzed using Paired Sampel T-Test assisted by SPSS Program in order to look at the effect of the treatment with herbal medicine on the hemoglobin levels.The research results indicated that in the intervention group the mean level of Hb before the intervention was 10.19 gr/dl and it increased after the intervention to 11.4 gr/dl,while in the control group before the intervention the mean value of hemoglobin 10.4 gr/dl and after the intervention was 10.9 gr/dl thus,the research result indicated the correlation between herbal medicine and hemoglobin level in teenagers (p= 0,000). Keywords : Teenagers, herbal, Hemoglobin, Anemia